The complete chloroplast genome sequence of Gelidocalamus xunwuensis (Bambusoideae: Arundinarieae): a shrubby bamboo endemic to China. Issue 2 (3rd July 2019) - Zhang, Yi-Ting; Guo, Chun-Ce; Yang, Guang-Yao; Yu, Fen; Zhang, Wen-Gen
Abstract: The complete chloroplast genome sequence of Gelidocalamus xunwuensis, firstly determined here, is 139, 705 bp in length, inclusive of a pair of inverted repeat (IR, 21, 817 bp) regions separated by a small single copy (SSC, 12, 803 bp) and a large single copy (LSC, 83, 268 bp). It contains 132 genes, such as 85 CDS, 8 rRNA genes, and 39 tRNA genes, respectively. The phylogenetic analysis shows that G. xunwuensis is highly clustered in the shibataea clade (III) of Arundinarieae, sister to the clade of G. tessellatus + Ferrocalamus rimosivaginus .